Electron spin polarization of the oxidized primary electron donor in reaction centers of photosynthetic purple bacteria - vandenBrink, J; Hermolle, T; Gast, P; Hore, P; Hoff, A (1996)
Fast time-resolved EPR spectroscopy is used to study electron spin polarization (ESP) in perdeuterated native, Fe2+-containing reaction centers (RCs) of photosynthetic purple bacteria. The spin-correlated radical pair(SCRP) model (previously used to simulate ESP observed in Fe-depleted RCs (Höre, P. J.; Hunter, D. A.; McKie, C. D.; Hoff, A. J. Chem. Phys. Lett. 1987, 737, 495) is extended to include the large anisotropy arising from the magnetic interactions between Fe2+ and the reduced primary electron-acceptor quinone (QA'~), which results in different quantization axes for the P+ and the (QA~Fe2+) spins. Using spectral simulations, it is shown that the ESP spectrum is solely due to the P+ part of the spin-correlated radical pair [P+(QA~Fe2+)], whereas the rapid decay of the spin-polarized signal is due to spin-lattice relaxation of the (QA~Fe2+) complex. The simulations are very sensitive to the relative orientation of the g matrices of P+ and (QA'~Fe2+). Using orientation II of the g matrix of the oxidized primary donor P+ (Klette, R.; Törring, J. T.; Plato, M.; Möbius, K.; Bönigk, B.; Lubitz, W. J. Phys. Chem. 1993, 97, 2015), the orientation of the g matrix of (QA~Fe2+) is assessed. Finally, it is shown that the ESP spectrum of perdeuterated native, Fe2+containing RCs of Rhodopseudomonas (Rps.) 'viridis is virtually identical to the spectrum obtained for perdeuterated native Rhodobacter (Rb.) sphaeroides, showing an AEA pattern (A denotes absorption and E emission). This result indicates that the magnetic axes of P+ and (QA'"Fe2+) have (nearly) the same directions relative to one another in both species. © 1996 American Chemical Society and Notes.